Penerapan Sistem Kontrol Adaptif Proportional Integral Derivative (PID) pada Mesin Penimbang Mie dengan Konveyor - Dafid, Ach; Umam, Faikul; Budiarto, Hairil (Rekayasa, 2025)
Indonesia is the second-largest instant noodle consumer in the world after China, with consumption reaching more than 12 billion packs per year. This high demand drives the need for innovation in the production process, especially in the weighing and cutting aspects, which are still carried out manually in small and medium industries. Manual processes not only require more time and energy, but also result in variations in packaging weight that are not uniform and reduce production efficiency. This study aims to design and implement a Proportional Integral Derivative (PID) adaptive control system on a noodle weighing machine with a conveyor. The system was developed using a load cell sensor to measure the noodle dough weight, a servo motor as a cutting actuator, and a DC motor as a conveyor drive, all of which are controlled by an Arduino ATmega 2560 microcontroller. The research methodology includes mechanical design, electronic design, control system programming, sensor calibration, and performance testing. The test results show that the system is able to produce noodle portions with a target weight of 50 grams consistently. The prototype has conveyor dimensions of 100×20×8 cm with a speed of 26 cm/ms, controlled using tuned PID parameters (Kp=1.5; Ki=1; Kd=1.7). From 20 trials, the system produced an average error of 0.75% and a success rate of 99.25%. Thus, the application of the PID adaptive control system has been proven to improve weighing precision, conveyor speed stability, and production efficiency. This innovation is expected to be a simple and affordable solution to support the automation of small and medium industries in Indonesia in facing increasingly fierce food market competition.